Multiple thermal spin transport performances of graphene nanoribbon heterojuction co-doped with Nitrogen and Boron - Hai Huang (Nature Portfolio, 2017)
Abstract Graphene nanoribbon is a popular material in spintronics owing to its unique electronic properties. Here, we propose a novel spin caloritronics device based on zigzag graphene nanoribbon (ZGNR), which is a heterojunction consisting of a pure single-hydrogen-terminated ZGNR and one doped with nitrogen and boron. Using the density functional theory combined with the non-equilibrium Green’s function, we investigate the thermal spin transport properties of the heterojunction under different magnetic configurations only by a temperature gradient without an external gate or bias voltage. Our results indicate that thermally-induced spin polarized currents can be tuned by switching the magnetic configurations, resulting in a perfect thermal colossal magnetoresistance effect. The heterojunctions with different magnetic configurations exhibit a variety of excellent transport characteristics, including the spin-Seebeck effect, the spin-filtering effect, the temperature switching effect, the negative differential thermal resistance effect and the spin-Seebeck diode feature, which makes the heterojunction a promising candidate for high-efficiently multifunctional spin caloritronic applications.